Emerging treatments for bacillus Calmette–Guérin-unresponsive non-muscle-invasive bladder cancer - Kim, Hyung Suk (Investig Clin Urol, 2021)
Intravesical bacillus Calmette–Guérin (BCG) immunotherapy has been the gold standard adjuvant treatment for intermediate- and high-risk non-muscle-invasive bladder cancer (NMIBC) after transurethral resection of bladder tumor (TURBT). BCG immunotherapy prevents disease recurrence and progression to muscle-invasive disease following TURBT. Although most patients initially respond well to intravesical BCG, considerable concern has been raised for patients with BCG failure who are refractory or recur in 6 months after their last BCG, which implies ‘BCG-unresponsiveness’. Based on current clinical guidelines, early radical cystectomy (RC) is recommended to treat BCG-unresponsive NMIBC. However, due to the high risk of morbidity and mortality of RC and patients' desire to preserve their own bladder, there is a critical unmet need for alternative conservative treatments as bladder-sparing strategies in BCG-unresponsive patients. Trials for effective bladder-sparing treatments are ongoing, and several novel agents have been recently tested in the NMIBC setting. The goal of this review is to introduce and summarize recently reported novel and emerging drugs and ongoing clinical trials for BCG-unresponsive NMIBC.